Hypocholesterolemic effect of red pitaya (Hylocereus sp.) on hypercholesterolemia induced rats - Rohin, Mohd Adzim Khalili; Ali, Abd Manaf; Abd. Hadi, Norhayati; Mat Hasan, Siti Asmah (2009)
This study was carried out to evaluate the total phenolic content and anti-oxidant activity of methanolic extract of red pitaya, and hypocholesterolemic effect of red pitaya (Hylocereus sp.) on lipid profiles status on hypercholesterolemia induced rats. From the analysis, total phenolic content in red pitaya is 46.06 ± 1.77 mg GAE/100 g fresh weight and antioxidant activity is 76.10% using FTC method. TBA analysis also showed red pitaya extract had high antioxidant effect (72.90%). An in-vivo study also showed red pitaya has hypocholesterolemic effect on induced hypercholesterolemia rats. After 11 weeks of study, total blood cholesterol significant decrease (p<0.05) in the groups supplement with red pitaya. The total cholesterol (TC) level for group PF1 were reduced from 3.356 mmol/L to 1.707 mmol/L (49.14%), group PF2 reduced from 3.435 mmol/L to 1.487 mmol/L (56.72%) and group PF3 reduced from 3.448 mmol/L to 1.412 mmol/L (59.06%) as compare to baseline respectively. The mean total cholesterol level in both negative (N – 5.12%) and positive controls (group HC – 13.79%) were not significantly different (p<0.05). The mean triglycerides (TG) level for all groups had shown a reduction (p<0.05) with value of 23.87% (group N), 22.674% (group HC), 42.81% (group PF1), 52.82% (group PF2) and 59.52% (group PF3) as compare to baseline levels. The mean HDL level increased by about 2.12% (group N), 19.31% (group PF1), 21.93% (group PF2) and much higher increase in group PF3 (34.42%). The mean LDL decreased by about 39.06% (PF3), 15.10% (PF2), 1.50% (PF1) and 4.33% (group N). The positive control has showed significantly increase with the mean value for 25.68%. In conclusion, all groups that received red pitaya supplementation has high antioxidant properties and showed a good results in managing of lipid profile. It was suggested that the consumption of red pitaya demonstrated the potential to reduce dyslipidemia and play a role in the prevention of cardiovascular disease.